O patrimônio na composição do mundo comum: outra topografia, novas paisagens - Amanda Alves Maciel Rocha (2023)
Cultural Heritage has been strategically appropriated as an instrument of resistance and political confrontation by historically subjugated groups, especially when the threats suffered reveal themselves as products of the very modern-capitalist logic from which it emerges. However, an “idea of heritage” established among non-European peoples does not always converge with what is implemented by the State and civil society as heritage. The heritage recognized by Governments carry with it a common principle that says a lot about its effects: they are supported by law, modern sciences and carry with them the notion of property. Thus, at the moment when Heritage turns to the “other” — desiring its presence in the organization of public life — its concepts, categories and ways of doing things are shaken and do not seem to sustain its new political commitment. In light of this, this thesis aims to describe the movement of concepts composition and categories that integrate the Heritage frameworks — formerly Historical and Artistic Heritage, today Cultural Heritage — and to reflect on its effects. To do so, we transform some of these concepts and categories of Heritage into objects of study — refraining from mobilizing them as an explanatory resource — and we reflect to what extent the description of this movement allows us to rethink the performance of Heritage in the task of progressive composition of a common world. Our methodology incorporates references from the Actor-Network Theory and seeks, from different reports and inscriptions, following the actors who perform these concepts, who inhabit these categories and who intend the Heritage network. Faced with the ecological crisis that plagues us, we urgently need to create spaces capable of contemplating collectives “whose competences were rejected, believing that our first duty was to first remove them from archaism, modernizing them” (LATOUR, 2019a, p. 389). Our hope is that the rich experience of Heritage, as long as it is revisited, intensified and reported by different actors, can serve this task.